Optimalisasi Pengelolaan Keuangan Klinik Zarzia Tasikmalaya Melalui Program Sosialisasi Dan Pelatihan Pencatatan Akuntansi - Surayuda, Rama Nugraha Irawan; Gandana, Ega; Rohmaniyati, Mela (Journal of Empowerment Community, 2026)
Financial statement are one of an important factor which is needed by many business people, including those in the healthcare sector. Zarzia Clinic is a clinic that provides various medical services, such as outpatient care, circumcision, inpatient care, and a 24-hour emergency room. Zarzia Clinic has difficulty in recording financial transactions in a regular and structured manner. This community service activity was carried out on October 15, 2025, with the aim of providing information and training on accounting records so that Zarzia Clinic managers could better understand and be able to keep accounting records, including preparing financial statements properly. The methods used in this activity were information sharing, guidance, and training, which were carried out from October 15 to 30, 2025. The results of this activity showed an increase in participants' understanding of the importance of accurate financial recording in accordance with applicable accounting standards, as well as their ability to compile accurate and transparent financial reports. At the end of the training, participants were given a test to measure their understanding, and the results showed that most participants were able to perform well, which was then verified through cross-checking by the owner of the Zarzia Clinic.